1973
DOI: 10.1111/j.1432-1033.1973.tb02903.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of Methionyl‐tRNA Synthetase from Escherichia coli

Abstract: Titration of native methionyl‐tRNA synthetase from Escherichia coli with tRNAfMet and tRNAmMet leads to 37% and 38% quenching of the enzyme fluorescence respectively. The quenching curves for the two tRNAs are not additive. Analysis of the binding data indicates the presence of a single site for tRNA per mole enzyme, with a three‐fold higher affinity for tRNAmMet. The tRNA binding parameters do not vary significantly in the presence of a saturating concentration of methionine. On the other hand, titration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0

Year Published

1974
1974
1993
1993

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 35 publications
(9 reference statements)
9
63
0
Order By: Relevance
“…Therefore the possibility remains that in these cases also pre-formed Pi reacts with the enzyme-bound adenylates and that the degradation of Ap4A to ADP is due entirely to a reaction between Pi and the adenylate, just as the ADP synthesis catalyzed by aminoacyl-tRNA synthetase in general may occur by this reaction. In this context it is also interesting that Blanquet et al [30] found that phosphate buffer inhibits the aminoacylation of tRNA'", in close agreement with competition from Pi for the enzymebound aminoacyl adenylate, as observed here.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore the possibility remains that in these cases also pre-formed Pi reacts with the enzyme-bound adenylates and that the degradation of Ap4A to ADP is due entirely to a reaction between Pi and the adenylate, just as the ADP synthesis catalyzed by aminoacyl-tRNA synthetase in general may occur by this reaction. In this context it is also interesting that Blanquet et al [30] found that phosphate buffer inhibits the aminoacylation of tRNA'", in close agreement with competition from Pi for the enzymebound aminoacyl adenylate, as observed here.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that this enzyme is functionally a dimer having two binding sites for methionine and methioninyl adenylate [55] and two for tRNAMet [56]. However, equilibrium dialysis experiments show that there are four distinct binding sites for ATP, only two of which are catalytic sites involved in methionyl adenylate formation (Fayat, G., Waller, J. P., unpublished results); it is these two sites which have been directly examined in the present study.…”
Section: Modifications To the Ribosementioning
confidence: 74%
“…However, the cishydroxyl arrangement is not essential, for the ribose can be replaced by arabinose (compound36), containing trans-hydroxyls, with only a seven-fold increase in inhibition constant. It is not surprising to observe that L-adenosine [56], the enantiomer of the naturally occurring adenosine, is not an inhibitor. This compound contains all the groups necessary for recognition, but the considerable change in their spatial distribution places them in positions not available for efficient binding to the enzyme.…”
Section: Modifications To the Ribosementioning
confidence: 99%
“…The HDO signal in the 'H-NMR spectrum was thus kept at a minimum. Concentrations of the enzymes and the nucleotides were measured spectrophotometrically using the data: A2mggi;'' = 1.39 cm-' (methionyl tRNA synthetase; molecular mass 152 kDa [30], 1.72 cm-' (truncated methionyl tRNA synthetase, molecular mass 64 kDa) and 0.54 cm-' (pyruvate kinase; molecular mass 238 kDa) [31], and AyF9 = 15.4 cm-for ATP. Pyruvate kinase is a tetramer with one catalytic MgATP binding site/subunit.…”
Section: Nmr Samplesmentioning
confidence: 99%